(untitled) (Research, Society and Development, 2021)
The objective of the study was to evaluate the effects of the use of chemical conditioners on poultry litter and their influence on the release of ammonia. Five chemical conditioners were used: hydrated lime, agricultural gypsum, aluminum sulfate, simple superphosphate and calcitic limestone, with different treatments in the split of the dose: in single dose, divided in two times and divided in three times. The treatments were added in the interval between batches. From each experimental unit a sample was collected and used for chemical analyzes of pH, moisture and volatilized ammonia. A completely randomized design was used in a factorial scheme with four replications, with factor "A" consisting of 16 treatments (five chemical conditioners and three forms of installment plus one control) and a "B" factor composed of five lots Evaluated (1st, 4th, 5th, 7th and 8th). Among the conditioners and ways of splitting the dose used, aluminum sulfate presents a greater magnitude in the decrease of pH and volatilization of ammonia, especially when applied in a piecemeal way.